Implementation of Pancasila Education Based on Sufism Values in Preventing Religious Radicalism at Muhammadiyah 1 Pamekasan Junior High School - Bastami, Bastami; Romelah, Romelah; Humaidi, M. Nurul (ISTAWA, 2024)
The rise of the doctrine of religious radicalism in this country has resulted in terror everywhere. Therefore, so that the next generation is not haunted by anxiety, it is necessary to educate students at school. So one proof of rejection of the doctrine of religious radicalism is carried out by Muhammadiyah 1 Pamekasan junior high school by implementing Pancasila education based on Sufism values. The approach used in this research uses a descriptive qualitative approach with a case study-based field research type. While the data collection technique uses observation, interview, and documentation techniques. Data analysis in this study used data reduction techniques, data presentation, and conclusion drawing. So that the results of this study found that the root causes of the doctrine of religious radicalism in the perspective of teachers and students are due to three aspects, namely religious, economic, and political fanaticism and monopolizing truth through sacred texts. The implementation of Pancasila education based on Sufism values at Muhammadiyah 1 Pamekasan Junior High School is through the value of Divine Sufism and the value of Insaniyah Sufism in the form of daily activities such as congregational prayers, recitation of yellow books, extracurricular programs, leadership and management training and so on.